Pedagogical bases of scientific organization of physical education lessons and sports lessons in general secondary schools Features of workload in physical education lessons - F I Ismailov; A U Yuldashov (Genius Journals, 2022)
Pedagogical bases of scientific organization of physical education lessons in general secondary schools and features of workload
Keywords: Physical education in general secondary schools; pedagogical bases of scientific organization of sports lessons; features of workload in physical education classes